A fast and efficient load flow technique for unbalanced distribution system. (January 2017) - Ghatak, Ujjwal; Mukherjee, V.
Highlights: Calculates the bus voltages in a single step. A generalized algorithm is proposed to construct the load impedance matrix. Special treatment to analyze weakly meshed network is also proposed. The proposed approach is faster than the conventional techniques. The proposed technique is robust enough to solve practical networks with accuracy. Abstract: This paper presents a fast and efficient load flow technique for unbalanced distribution system. The proposed load flow technique is derived by promulgating the concept of conventional backward forward sweep (BFS) technique of power flow study for distribution system. The proposed technique employs a novel load-impedance matrix (LIM) to calculate the bus voltages in a single step unlike the conventional BFS approach which involves two separate steps (backward sweep and forward sweep) to perform the same and this improvement is claimed as the novelty of this work. This distinctive feature makes the proposed algorithm faster in operation. Nodal voltages, at any iteration, may be calculated, directly, from the values obtained in the previous iteration by utilizing LIM. A simple concept of set theory is adopted here to construct the LIM. Special treatments are also included in this method to analyze weakly meshed systems. The proposed technique is flexible enough to accommodate any sort of changes in the existing network topology through LIM. It is tested on different three-phase balanced and unbalanced radial distribution systems as well as weakly meshed networks for load flow study. A separate case study is also presented to check the validity of the proposed load flow technique for various transformer connections. The obtained results demonstrate the effectiveness of the proposed technique. Furthermore, performance comparison reveals that the proposed algorithm is, computationally, faster and robust than the conventional power flow techniques reported in the recent state-of-the-art literatures.